A Study of Self and Solute Diffusion in Pure Zirconium and Dilute Zirconium-Cobalt Alloys - Kidson, Geoffrey (My University, 1968)
The diffusion coefficient of Co has been measured as a function of temperature in the body-centered-cubic phase of 99.99% zirconium. The diffusion rates are extraordinarily large, and follow the relation D = [3.26 ± 2.77] x 10^(-3) exp -(21,820 ± 960/RT) cm^2 /sec over the range 900 to 1600°C.
The Arrhenius plot has a positive curvature above 1600°C. The influence of cobalt additions on the diffusion of 95 ZR and 60 Co in dilute Zr-Co alloys was studied from 0 -2 at.% cobalt at 933°C. A theoretical model was developed to relate the effect to the solute correlation factor. It is established that diffusion in these systems cannot be accounted for in terms of a vacancy mechanism alone. Other models are discussed.
Keywords: diffusion; zirconium alloys; pure zirconium; cobalt